Tinjauan Kuantitatif Tentang Faktor-Faktor Kepemimpinan Yang Mempengaruhi Kinerja Organisasi - Rizqi, Muhammad; Heryanti, Andini Dwi; Said, Yasir; Hidayatun, Nurul; Wijaya, Muhammad Adhimawan (Peneliti.net, 2025)
This study aims to quantitatively evaluate the leadership factors that influence organizational performance. Through statistical approaches and data analysis, the study identifies key variables related to leadership effectiveness and how these variables impact organizational performance. The factors analyzed include leadership styles, communication, decision-making, motivation, and team development. Data were collected through surveys from various organizations in the industrial and service sectors. The results show that transactional and transformational leadership styles have a significant influence on organizational performance. Additionally, effective communication and participative decision-making were found to be major determinants of high performance. This study provides valuable insights for management practitioners in improving organizational performance through the development of more effective leadership, focusing on enhancing communication and employee involvement in decision-making processes.